Causal Treatment of Inflammatory Diseases of ENT organs — Complications of Acute Respiratory Infection - Ye.Yu. Radtsig; N.V. Yermilova; L.V. Malygina; О.V. Bugaichuk; Ye.P. Sel’kova (Вопросы современной педиатрии)
Inflammatory diseases of ENT organs often complicate the course of acute respiratory infections in children and remain one of the most common causes of prescribing antibacterial drugs. The article describes the results of analyzing an antiviral therapy in patients with acute uncomplicated rhinosinusitis (n = 175) and non-perforated form of acute otitis media (n = 71). It was shown that, irrespective of diagnosis, the children were most commonly prescribed with rimantadine and homeopathic remedy produced by Boiron. The administration of antibacterial drugs was initiated in 38% of patients with acute otitis media. No deterioration on the background of receiving drugs with antiviral activity was observed in patients with acute rhinosinusitis. In general, a low patient compliance to antiviral therapy can be noted. This problem can be solved by prescribing short-course drugs.